PENGARUH PEMBELAJARAN DI RUANG TERBUKA HIJAU TERHADAP MOTIVASI BELAJAR SISWA (Jurnal Tata Kelola Pendidikan, 2020)
The development of facilities and infrastructure that is increasingly being carried out inurban areas and the rapid growth of population causes limited green open space. Greenopen space itself has many benefits if its existence is cared for and managed well. Greenopen spaces are also being intensely procured in cities, provinces and schools. It is knownthat if a green open space is provided at school it can be one of the learning resources thatcan optimize learning achievement. Because unwittingly green open space which containsa place to grow plants with a green color that can reduce boredom when students feelmonotonous learning activities. So it is hoped that the opening of green open land inschools as a source of learning can increase student motivation and can improve student’scritical thinking processes about everyday phenomena.
Keywords: Optimalization of Green Space; Student Learning Motivation; Learning ased on environment